1880 R.I. Pub. Laws 110, ch. 806, § 3 - (:unkn) unknown (General Publisher, 1880)
Any tramp who shall willfully[1] and maliciously injure any person where such offence is not now punishable by imprisonment in the state prison, or who shall be found carrying any firearm or other dangerous weapon, shall be punished by imprisonment in the state prison not more than three years.
--
Keywords: CARRY - DANGEROUS PERSONS